Gender-role Incongruity and Audience-based Gender Bias: An Examination of Networking among Entrepreneurs - Abraham, Mabel (Administrative Science Quarterly, 2020)
While most research explaining the persistence of gender inequality has focused on how decision makers’ own biases perpetuate inequities, a growing body of work points to mechanisms of bias that may arise when a decision maker is concerned with satisfying a third party or audience. Using data from 2007 to 2013 on 2,310 members of a popular networking organization for entrepreneurs, I examine the extent to which the presence of third parties leads to gender inequality in resource exchange, or connections to potential clients. I show that decision makers are most apt to favor male network contacts in exchanges involving a third party when considering whether to connect a contact in a male-typed occupation. Decision makers do not display this gender bias in exchanges that do not involve a third party or when sharing connections to potential clients with contacts in gender-neutral or female-typed occupations. This setting offers a unique opportunity to compare gender inequality in exchanges involving a third party with cases that do not involve a third party, providing direct evidence of the effects of audiences or third parties for gender inequality.